Ecclesiastical Elitism and the Church's Ambivalent Theology of Temporalities - Abellanosa, Rhoderick John S. (Concilium, 2023)
This work is an invitation to further the discussion from the narrowed down focus on clerical sexual abuse to ecclesial elitism that is strengthened and sustained by the Church's financial resources, properties, and economic connections. The first main part expounds the notion of ecclesiastical elitism. The second part proposes a critique of the Church's ambivalent theology of temporalities. It is argued that the ambivalence in the Church's theology of temporalities is necessary if a broader critique is to be made on the current crisis of ecclesiastical elitism.